2020
DOI: 10.7899/jce-19-8
|View full text |Cite
|
Sign up to set email alerts
|

Grit and chiropractic students' academic performance: a cross-sectional study

Abstract: Objective Previous investigations have studied the relationship between grit and academic performance, and it has been reported that grittier students perform better academically. The objectives of this study are to measure chiropractic students' grittiness and to explore the correlation between grit and academic performance. Methods We distributed the Short Grit Scale (Grit-S) questionnaire to chiropractic students in electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
13
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 25 publications
3
13
0
1
Order By: Relevance
“…Overall, the findings support the Seventh Grade Mindset/Resiliency Curriculum at the target school and the importance of grit and locus of control in academic achievement. These results support existing literature regarding the beneficial impact of grit and locus of control on academic achievement (Alzerwi, 2020;Datu et al, 2018;Duckworth & Quinn, 2009;Miller-Matero et al, 2018;Postigo et al, 2020;Pulkkinen & de la Ossa, 2021) and evidence suggesting that they are malleable and can be nurtured through educational interventions (Credé et al, 2017;Stoffel & Cain, 2018).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Overall, the findings support the Seventh Grade Mindset/Resiliency Curriculum at the target school and the importance of grit and locus of control in academic achievement. These results support existing literature regarding the beneficial impact of grit and locus of control on academic achievement (Alzerwi, 2020;Datu et al, 2018;Duckworth & Quinn, 2009;Miller-Matero et al, 2018;Postigo et al, 2020;Pulkkinen & de la Ossa, 2021) and evidence suggesting that they are malleable and can be nurtured through educational interventions (Credé et al, 2017;Stoffel & Cain, 2018).…”
Section: Discussionsupporting
confidence: 86%
“…Grit has predicted grade point average (GPA) in adolescents in public school (Duckworth & Quinn, 2009); university students in Ivy League and state colleges (Duckworth et al, 2007); Black male college students at a predominantly White college (Strayhorn, 2014); and doctoral students (Cross, 2014). Pulkkinen and de la Ossa (2021) found that graduate students with higher grit scores performed better academically than students with lower grit scores. Miller‐Matero et al (2018) and Alzerwi (2020) showed that students with higher levels of grit performed better in medical school and completed without repeating an academic year.…”
Section: Introductionmentioning
confidence: 99%
“…Scores are averaged to form an index of grit level 14. A mean score of 3.4 has consistently been reported in the general population, and scores of 3.7 and greater have been reported in health profession students 15–17…”
Section: Methodsmentioning
confidence: 99%
“…Remediation related to a competency-based curriculum is currently growing in medical education, but often lacks specific processes in nursing 21,22. For at-risk students, proactive metacognitive remediation strategies implemented early in the course may help to promote their success 8,16. A remediation program with strategies like identification of learning weaknesses and strengths, student-initiated learning plans, and practice questions may help the student mentally organize content and lead to a deeper understanding of what is being learned and lessen perceived stress 23,24…”
Section: Methodsmentioning
confidence: 99%
“…GRIT refers to passion and perseverance for long-term goals and was presented as a trait by leaders in various fields. 3 6 Passion is derived from the inner self, and this makes the person internalize an activity in terms of time and energy. Perseverance is a quality that motivates people not to give up when they face problems and challenges.…”
mentioning
confidence: 99%